2017
DOI: 10.3389/fneur.2017.00617
|View full text |Cite
|
Sign up to set email alerts
|

If Time Is Brain Where Is the Improvement in Prehospital Time after Stroke?

Abstract: Despite the availability of thrombolytic and endovascular therapy for acute ischemic stroke, many patients are ineligible due to delayed hospital arrival. The identification of factors related to either early or delayed hospital arrival may reveal potential targets of intervention to reduce prehospital delay and improve access to time-critical thrombolysis and clot retrieval therapy. Here, we have reviewed studies reporting on factors associated with either early or delayed hospital arrival after stroke, toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 149 publications
4
69
1
10
Order By: Relevance
“…Therefore, OTT might significantly affect the rate of END occurring after thrombolytic therapy, and the rate might increase with the increase of OTT. Pulvers and Watson () reported that emergency medical pathways, stroke symptomatology, patient and bystander behavior, patient health characteristics, and stroke treatment awareness might affect OTT, and reducing OTT might improve the stroke outcomes, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, OTT might significantly affect the rate of END occurring after thrombolytic therapy, and the rate might increase with the increase of OTT. Pulvers and Watson () reported that emergency medical pathways, stroke symptomatology, patient and bystander behavior, patient health characteristics, and stroke treatment awareness might affect OTT, and reducing OTT might improve the stroke outcomes, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, OTT might significantly affect the rate of END occurring after thrombolytic therapy, and the rate might increase with the increase of OTT. Pulvers and Watson (2017) reported that emergency medical pathways, stroke symptomatology, patient and bystander behavior, patient health characteristics, and stroke TA B L E 3 The results of subgroup analysis F I G U R E 3 Sensitivity analysis of the rate of early neurological deterioration occurring after thrombolytic therapy our results in this meta-analysis did not conform to these conclusions. In the present subgroup analysis by NIHSS at admission, the rate of END occurring after thrombolytic therapy of the patients with NIHSS at admission ≤4.0 was highest among the three groups, which is inconsistent with most literatures.…”
Section: Discussionmentioning
confidence: 80%
“…En nuestro trabajo concluimos que llegar por propios medios se asoció a un menor tiempo de llegada, comparado con acceder al hospital en ambulancia, lo que es discordante con varias publicaciones 5,6,18 . Esto pudiera explicarse por el déficit de ambulancias en el sistema público chileno, comparado con países desarrollados.…”
Section: Discussionunclassified
“…Dentro de los factores más frecuentemente asociados con una llegada precoz al SU de pacientes con ACV agudo destacan: llegada en ambulancia, severidad del ACV, sintomatología, subtipo de ACV, comorbilidades, comportamiento o percepción del paciente y/o familiar al inicio del cuadro y horario de inicio de los síntomas 20 . De los factores asociados a retraso en la llegada de los pacientes destacan: sexo, raza, medio de llegada e historia de enfermedad cardiovascular 21 .…”
Section: Introductionunclassified